Hydrodilatation and Intra-articular Steroid Injection are Both Effective in Management of Frozen Shoulder: A Case Series - Butarbutar, John Christian Parsaoran; Riantho, Albert; Fidiasrianto, Kevin; Rizky, Dio Asgira (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Frozen shoulder is a common problem in general orthopaedic practice, affecting about 2% of the population. Intra-articular corticosteroids (IA) and hydrodilatation have been reported as more effective among other conservative treatments. However, it is unclear which treatment is superior for frozen shoulder, and the hydrodilatation procedure leads to more discomfort in patients since it involves stretching of joint capsule. In this case series, we present 10 cases of frozen shoulder that were treated with hydrodilatation or IA steroid injection. The purpose of this study is to show the effectiveness of hydrodilatation and IA steroid injection in managing patient with frozen shoulder.Methods: This study was a retrospective case series of patients who received IA steroid injection or hydrodilatation. Five patients underwent IA steroid injection, and another five patients underwent hydrodilatation. The American Shoulder and Elbow Score (ASES) was used to evaluate each patient before and six months after treatment.Result: Hydrodilatation and IA steroid injection showed significant improvement in ASES score assessed at 6-month follow-up.Conclusions: Hydrodilatation and IA steroid injection are both effective to treat frozen shoulder in long term follow up.